2006
DOI: 10.1007/bf02913067
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid in cardiovascular diseases

Abstract: Sialic acid, the acylated derivatives of 9-carbon sugar neuraminic acid, present as terminal component of oligosaccharide chains of many glycoproteins and glycolipids, has been recognized to be involved in the regulation of a great variety of biological phenomena. Studies have shown that serum sialic acid predicts both coronary heart disease and stroke mortality and reflects the existence or activity of an atherosclerotic process. Most of the studies have shown an elevation in serum sialic acid concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 73 publications
2
26
0
3
Order By: Relevance
“…[15,16,18] The higher prevalence of small dense LDL has been associated with cardiovascular events, acute ischemic stroke onset, and short-term mortality after acute ischemic stroke. [33][34][35][36] Our data demonstrate that in the blood of the same patient, there are at least two distinct forms of LDL differing by particle size and density. Obviously, the LDL pattern would strongly depend on what LDL fraction prevails in circulation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[15,16,18] The higher prevalence of small dense LDL has been associated with cardiovascular events, acute ischemic stroke onset, and short-term mortality after acute ischemic stroke. [33][34][35][36] Our data demonstrate that in the blood of the same patient, there are at least two distinct forms of LDL differing by particle size and density. Obviously, the LDL pattern would strongly depend on what LDL fraction prevails in circulation.…”
Section: Discussionmentioning
confidence: 98%
“…[12,23,32] Several studies have reported an elevation of sialic acid serum levels in CHD patients, and also on its correlation with the severity of the coronary lesions. [33] Diabetic patients' LDL, by the first approach, appeared to have a decreased level of sialic acid, and further investigations have shown that this was due to an increased proportion of desialylated LDL fraction in patients' blood and a greater extent of its desialylation. [13,14] This LDL fraction was also characterized by increased non-enzymatic glycation and altered lipid composition, namely, decreased content of esterified cholesterol and elevated level of lyso-phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Sialic acids, which is found in surface of several cells and its responsible for antigenic characteristic, should be an important component of glycolipids and glycoproteins (21). It is found in several fluids such as plasma, gastric secretion, urine and also tissues such as erythrocyte, leucocytes, colon, and stomach in the body (14). Serum sialic acid level was increased in certain diseases and it might be used as a tumor marker in several diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis showed that the NaF group was significantly higher than the control group with regards to LSA (17 (13). Studies have also shown that serum total sialic acid is elevated in cardiovascular disease (14). Purpose of our study is to investigate effect of resveratrol on LSA and TSA levels in chronic fluorosis.…”
Section: Introductionmentioning
confidence: 99%
“…10 The sialic acid levels may be influenced by inflammation, neoplastic or inborn genetic disorder. 11 It is found that Sialic acid can be used as a measurement of the acute phase response because many proteins of the immune response are actually glycoproteins, and these glycoproteins have sialic acid as the terminal sugar on their oligosaccharide chain. Serum sialic acid is a marker of the acute-phase response being produced by the liver, stimulated by proinflammatory cytokines such as interleukin-1, interleukin-6, and tumor necrosis factor-α.…”
Section: Classification Of Severity Of Airflow Limitation In Copdmentioning
confidence: 99%